2018
DOI: 10.5582/ddt.2018.01040
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial polysaccharides inhibit sucrose-induced hyperglycemia in silkworms

Abstract: Diabetes and obesity result from sucrose-induced hyperglycemia. Prevention of hyperglycemia contributes to inhibit the onset of these life-related diseases. Here we show that polysaccharides obtained from soil bacteria inhibit sucrose-induced hyperglycemia in an in vivo silkworm evaluation system. Ethanol precipitates of extracellular polysaccharides were prepared from viscous bacterial colonies. Among 24 samples obtained from different bacterial species, oral administration of 6 samples from Rhizobium altipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Silkworms are useful for large-scale in vivo evaluation because they are inexpensive and can be reared in large groups (21)(22)(23)(24)(25)(26)(27). We reported the discovery of several active substances that suppress postprandial hyperglycemia using the silkworm evaluation system (4,11,28). The inhibitory effects of each of the four natto products we examined on sucrose-induced hyperglycemia in silkworms differed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silkworms are useful for large-scale in vivo evaluation because they are inexpensive and can be reared in large groups (21)(22)(23)(24)(25)(26)(27). We reported the discovery of several active substances that suppress postprandial hyperglycemia using the silkworm evaluation system (4,11,28). The inhibitory effects of each of the four natto products we examined on sucrose-induced hyperglycemia in silkworms differed.…”
Section: Discussionmentioning
confidence: 99%
“…Two volumes of ethanol were added to the water extract fraction, and a filamentous precipitate was collected by centrifugation to obtain a water-soluble viscous fraction. Enzymatic treatment of the water-soluble viscous fraction was performed as described previously (11). The watersoluble viscous fraction was treated with DNase I (1,000 U/mL; Promega) and RNase A (10 μg/mL; NIPPON GENE CO., LTD.) for 24 h at 37°C, and then incubated overnight at 37°C with proteinase K (100 µg/mL).…”
Section: Preparation Of the Water-soluble Viscous Fraction And Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation methods using mammals, however, are not only expensive, but are also associated with ethical issues with respect to animal welfare. We previously reported that the silkworm, an insect larva, can be used to evaluate the effects of different hypoglycemic agents (3)(4)(5)(6)(7)(8)(9). Ingestion of sucrose rapidly increases the blood glucose level in silkworms, and acarbose and voglibose, α-glucosidase inhibitors used clinically for human patients, also suppress the increase in silkworms (3).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported diabetic silkworm models for evaluating anti-diabetic agents such as human insulin, pioglitazone, and metformin (6)(7)(8)(9). Moreover, we established a silkworm model to search for substances that suppress sucrose-induced hyperglycemia (10)(11)(12)(13). Enterococcus faecalis YM0831, a lactic acid bacteria strain that was identified using an in vivo silkworm evaluation system, suppresses sucrose-induced hyperglycemia in humans (14).…”
Section: Introductionmentioning
confidence: 99%